Modelling Islamic financial literacy / Wan Zulkipli Wan Salleh, Wan Siti Esah Che Hussain, Wan Asma’ Wan Abu Bakar - Wan Salleh, Wan Zulkipli; Che Hussain, Wan Siti Esah; Wan Abu Bakar, Wan Asma’ (Institute of Research Management & Innovation (IRMI), 2014)
Financial literacy has been discussed widely in western countries as reports on bankruptcies and high debt is escalating. Studies found that one main reason was financial illiterates. However, no or very limited study had been done to look into the Islamic financial literacy subject matter even though the Islamic finance products are flourishing the market today. As the Islamic financial systems and terms become more complex for the layman to understand its products and operations, it is not surprising for people to make wrong decision in saving and managing their financial issues. As Muslims, apart from having knowledge on finance, they must also acquire knowledge on the syariah aspect regarding finance. Thus, this research has examined the level of Islamic financial literacy among students in UiTM Kedah branch and also identifies the demographic factors that affecting the literacy among them. A new model was established that depicts the relationship between Islamic financial literacy, demographic factors and financial behavior of Muslims. This model is hoped to be a catalyst for exploring new ideas and concept on Islamic financial literacy as literature on such area is limited. Cluster sampling technique was used onto UiTM students from different programs offered in this branch. Data collected using a set of questionnaire derived from literature research and then analyzed using descriptive measure and model it via Multiple regression method. It was found that majority of the students have average knowledge on Islamic financial and the terms used in its operation. There was significant difference in level of knowledge between the programs and from the study, those students from business and finance department are of higher level of understanding compared to other non-business related programs. There was also significance difference between the level of knowledge and father’s education level. However, there was no difference between the level of knowledge and their mother’s education level. Those who enroll in the business program attained higher level of literacy compared to those enrolled into non-business programs and thus becomes the most significant predictor of Islamic financial literacy.